Елліністична розписна кераміка з Ольвії - Котенко, В.В. (Археологія, 2022)
Стаття доповнює серію праць, присвячених дослідженню розписної кераміки з розкопок Ольвії. До
наукового обігу залучаються фрагменти виробів,
які за сукупністю характеристик зараховуються до херсонеського виробництва та засвідчують
міжполісні контакти в елліністичний час. Проаналізовано матеріали Наукових фондів Інституту археології НАН України. The article is devoted to the publication of a small collection of Hellenistic painted pottery from Olbia. The studying of certain categories
of archaeological material provides an opportunity to explore in detail the various aspects of their characteristics and to outline issues
related primarily to its origin. Among the promising vectors of the study of Olbian ceramic complex are finds of the Hellenistic period and
isolation of some series of imported pottery of the Black Sea North region production. One of the representative collections of Hellenistic
pottery from Olbia is stored in the Scientific Repository of the Institute of Archaeology of the National Academy of Sciences of Ukraine.
It is represented by materials of excavations of the second half of the 20th century. First of all, the so-called red clay painted pottery is very
interesting, the origin of which is still debated in historiography. Among the items selected for the study, table jugs predominate, which are
represented by a fairly wide range of variations of profile parts and ornamental compositions. The decorations are the following: encircling
lines, plant motifs or a combination of them; the painting is done mainly with dark red paint. The collection also includes fragments of
ceramic flasks, which are rare forms of ware in the Black Sea North region and were used as small containers. Profile parts of vessels are
described separately. The article also contains the description of the morphology of different types of jugs and their capacity.
Particular attention is paid to the origin of Hellenistic ceramics. It has been found that such pottery was probably made in Tauric Chersonesos.
Despite the need of chemical and technical analyses of the clay composition and clarification of the raw materials origin, it should be noted
that such indicators as mass character, typological similarity and the presence of these products in situ in the places of pottery production are
quite convincing factors in the process of their attribution. Its availability in the ceramic complex of Olbia testifies to the existence of interpoleis
contacts in the Black Sea North region, in particular to certain connections of this centre with Taurica in the 4th – 2nd centuries BC, which
has already been recorded archaeologically on the amphorae materials. Therefore, a representative collection of Hellenistic pottery from the
excavations at Olbia supplemented new information about the life of the polis during its active development.